2021
DOI: 10.1038/s41598-021-93538-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mitigation by digital contact tracing and contact prevention (app-based social exposure warnings)

Abstract: A plethora of measures are being combined in the attempt to reduce SARS-CoV-2 spread. Due to its sustainability, contact tracing is one of the most frequently applied interventions worldwide, albeit with mixed results. We evaluate the performance of digital contact tracing for different infection detection rates and response time delays. We also introduce and analyze a novel strategy we call contact prevention, which emits high exposure warnings to smartphone users according to Bluetooth-based contact counting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This raises the question of whether exposure notifications are reflective of an increased exposure risk [ 27 ]. Addressing this question is particularly relevant due to concerns that Bluetooth technology may not be able to capture exposure risks accurately [ 28 , 29 ]. By using data on digital proximity tracing app use with Venn diagrams, we presented a novel approach that evaluates the effect of exposure notifications on users’ mitigative actions as well as the risk of SARS-CoV-2 transmission through test positivity.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether exposure notifications are reflective of an increased exposure risk [ 27 ]. Addressing this question is particularly relevant due to concerns that Bluetooth technology may not be able to capture exposure risks accurately [ 28 , 29 ]. By using data on digital proximity tracing app use with Venn diagrams, we presented a novel approach that evaluates the effect of exposure notifications on users’ mitigative actions as well as the risk of SARS-CoV-2 transmission through test positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Low detection rates reduce the effectiveness of CTAs because contact tracing is impossible without a confirmed diagnosis, which is a serious challenge for both DCT and MCT. Previous research has shown that contact tracing barely reduces viral propagation when the detection rate is only 13%, and the effectiveness of contact tracing increases significantly when the detection rate increases to 26% or 37% [40]. In June 2020, the average detection rate worldwide was <10% and varied significantly among countries [41].…”
Section: Comparison With Prior Workmentioning
confidence: 98%
“…By now, numerous studies have been conducted regarding benefits and limitations of DCT concerning its use during the COVID-19 pandemic [10, [14][15][16][17][18][19][20][21][22][23][24]. Early studies suggested that containment might be possible with high app participation [10, 14,15] and assumed app participation rates of � 50% as achievable or even as lower bounds [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical results from Spain, Germany, and the UK suggest, however, that eventually participation rates of only ≈ 30% could be or were reached [ 11 , 24 , 25 ]. The fraction of sampled contacts scales quadratically with participation [ 10 , 18 , 22 , 23 ]. So, for instance, if a randomly selected 50% of the population participates, approximately 25% of all contacts occur between pairs of individuals that are users of a DCT application, while only 9% of all contacts are traceable if 30% participate, therefore already greatly diminishing the potential effect of the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation